Keterlibatan WHO dalam Penanganan Wabah Kolera di Nigeria Tahun 2018 - Yusuf, Affandi (Global and Policy Journal of International Relations, 2023)
Abstract The World Health Organization (WHO) is one of the organizations under the United Nations tasked with maintaining health security in the world. WHO's main mission is for all individuals around the world to have access to adequate health facilities without discrimination such as differences in ethnicity, race, religion, political choice, economy to regional borders. As an international organization, WHO has a very important role to help member states to solve health problems and provide leadership in decision-making, rule-making and health norms in the world. The cholera outbreak in Nigeria in 2018 became one of the health problems in various states and Local Government Areas (LGAs). The author uses the role theory of international organizations to explain the WHO's role in handling the cholera outbreak in Nigeria in 2018. The data used comes from literature studies, research journals, news as well as official data and press releases from the Nigerian government. The results of this study will shed light on WHO's role in handling the cholera outbreak in Nigeria in 2018.DOI: https://doi.org/10.33005/jgp.v11i01.3853